A mathematical model of the process of freeze-drying - Лиса, Яна Петрівна (Eastern-European Journal of Enterprise Technologies, 2015)
The study explores the process of freeze-drying of biological materials and the basic parameters that affect the quality of the original sample. We have considered the existing methods of controlling freeze-drying stages and their main limitations. The research findings will be used for modeling and optimizing the lyophilisation process. The paper focuses on the problem of monitoring the temperature of biological materials in vials during the freeze-drying. It is necessary to control the temperature of the product to keep it below the triple point (transition point) in order to avoid spoilage. It is also important to determine the position of the moving boundary of sublimation, which informs about completing the stage of primary drying. There are many models of developing temperature sensors, but none fully satisfies the needs of the process. Therefore, we have calculated a mathematical model that will be used further to develop a temperature sensor to control the process of sublimation. Our experimental study was processed in COMSOL Multiphysics 5.0 Final and tested at the State Scientific-Control Institute of Biotechnology and Strains of Microorganisms. The study has revealed a significant impact of the zone of acontact between the heater and the object of drying on the duration of dehydration (about 20%). The devised mathematical model will furtherallow conducting multivariate calculations aimed at minimizing energy consumption and choosing optimal treatment regimes in obtaining and maintaining a certain level of product quality. The suggested calculation method can help estimate the real duration of the vacuum freeze-drying,taking into account the conditions of the contact.